Trending screen addiction---emerging risk of increased virtual autism among toddlers - Rehan, Fatima; Nasrumminallah, Maryam; Mukhtiar , Sawairah (Journal of the Pakistan Medical Association, 2023)
only in Pakistan but worldwide. In Pakistan alone, approximately 33 million people suffer from Type 2 diabetes mellitus, with an additional 11 million adults with impaired glucose tolerance, while approximately nine million people with diabetes remain undiagnosed.1 Diabetes causes many fatal complications including hypertension, myocardial infarction, stroke, chronic kidney disease, neuropathy, etc. To lower the morbidity and mortality rates, prompt screening and treatment of complications of diabetes should be done, especially the lesser-known complications. In the past, a strong association between idiopathic pulmonary fibrosis and diabetes was noted by some physicians. This association was established by Stefan Kopf et al.2 More recently a study funded by Diabetes UK (a British-based patient, healthcare professional, and research charity) at the Imperial College of London claimed that there is a strong association between lung disorders and Type 2 diabetes mellitus.3 This study examined data from approximately 500,000 individuals in 17 large-scale investigations. According to the investigation, type 2 diabetics' elevated blood sugar levels directly affect lung function. For instance an increase in typical blood sugar levels from 4 mmol/L to 12 mmol/L. might cause a 20% decline in lung function and capacity. Dr. Ben Jones, Dr. Marika Kaakinen and Dr. Elizabeth Robertson were in pivotal positions in this research and they all quoted lung disorders occurring in Type 2 diabetic patients as a direct complication of diabetes.3 Rajasurya V et al defined diabetic lung or diabetic pneumopathy as a condition characterized by progressive lung disease caused by the microvascular complications associated with diabetes mellitus.4 The direct complications of diabetes mellitus in the lungs include interstitial lung disease and idiopathic pulmonary fibrosis. Interstitial lung disease involves different degrees of inflammation and fibrosis in the pulmonary parenchyma and Idiopathic pulmonary fibrosis involves chronic progressive fibrosis leading to progressive pulmonary failure.4 Knowing the extent of diabetic patients present in Pakistan and how quickly this number can escalate,5 a clinical trial should be replicated on a larger population. There is a need to establish protocols for screening of diabetes related pneumopathy. People should be educated about these lesser-known complications of diabetes, and diabetic patients should be trained to perform pulmonary function tests at home. Overall these measures will surely help to improve the quality of life of a diabetic patient and to reduce gross morbidity and mortality rates.